2015
DOI: 10.5367/te.2015.0480
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Analysis of Tourism Determinants in Sicily

Abstract: This study provides an initial analysis of the key determinants of tourism in Sicily. In doing so, it responds to the general lack of a scientific approach in the study and management of tourism in Sicily. By mixing a gravity approach and system dynamics methodology, the attractiveness of Sicily is examined, taking into account both structural and promotional aspects that might affect tourism demand. The results strongly suggest that the island's natural and cultural resources, the road infrastructure and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Seetanah et al (2010) found that the economic growth of South Africa, measured by real GDP per capita and tourism infrastructure, has a considerable positive impact on inbound tourism demand. In Provenzano’s (2015) study in Sicily, both inbound and domestic tourism were found to be affected by various supply-side factors, ranging from natural and cultural resources to road infrastructure and urban environment. Besides economic factors, many studies found that social and political factors are instrumental in determining tourism growth in developing countries (Eugenio-Martin et al, 2008; Khadaroo & Seetanah, 2008; Provenzano, 2015; Seetanah et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Seetanah et al (2010) found that the economic growth of South Africa, measured by real GDP per capita and tourism infrastructure, has a considerable positive impact on inbound tourism demand. In Provenzano’s (2015) study in Sicily, both inbound and domestic tourism were found to be affected by various supply-side factors, ranging from natural and cultural resources to road infrastructure and urban environment. Besides economic factors, many studies found that social and political factors are instrumental in determining tourism growth in developing countries (Eugenio-Martin et al, 2008; Khadaroo & Seetanah, 2008; Provenzano, 2015; Seetanah et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While tourism growth is intertwined with macroeconomic situations of both origin and destination countries, the long-run relationship between tourism demand and economic growth in empirical studies is far from clear (Crouch, 1994a, 1994b, 1996; Song, Wong, et al, 2003). Incorporating macroeconomic variables in model development is instrumental as research has verified the effect of economic development of destinations, including infrastructure and hotel supply, on tourism demand (Choi et al, 1999; Choyakh, 2008; Eugenio-Martin et al, 2008; Provenzano, 2015; Seetanah et al, 2015). Also, a close economic linkage between two countries, such as bilateral trade, may exert a positive externality on tourist flows between them not least because trade is the driving force of business travel between trading partners (Kulendran & Wilson, 2000a, 2000b; Kulendran & Witt, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The literature documents that public infrastructure is a determinant of economic growth and productive performance, but the magnitude and significance of this contribution are controversial (Holtz-Eakin, 1994; Hulten and Schwab, 1984; Nadiri and Mamuneas, 1994). Transport infrastructure affects the attractiveness of a country to international tourists (Eugenio-Martin, 2016; Provenzano, 2015; Seetanah and Khadaroo, 2009), and public transport connectivity attracts tourists from different travel distances (Yang et al, 2019). Roehl et al (1993) also find that areas with highly developed highway systems obtain more revenues from tourists.…”
Section: Model Description and Main Factorsmentioning
confidence: 99%
“…This framework has been extensively used for empirical exercises due to its goodness of fit, above all to explain international trade (Anderson and Wincoop, 2003). Since tourism is considered to be a special type of trade in services, gravity equations have also been used to estimate the magnitude of tourism flows in different contexts (Eilat and Einav, 2004;Fourie and Santana-Gallego, 2011;Fourie et al, 2015;Gálvez et al, 2014;Khadaroo and Seetanah, 2008;Kimura and Lee, 2006;Provenzano, 2015;Santana et al, 2010;Vietze, 2012). Although the application of the gravity equation method has been supported by the international trade theory, the use of a gravity equation in analyzing international tourism from a consumer theory perspective has recently been justified (Morley et al, 2014).…”
Section: The Gravity Modelmentioning
confidence: 99%